Drug Induced Immune Mediated Nephritis: Molecular Mechanism , Pathways and Clinical Implications - Prahala P.R; Samina Sameer; Sandra Pillai; Kiran K J; Prasobh G R; Anusha Jasmine; Kanthlal S K (International Journal of Toxins and Toxics, 2026)
Drug-induced immune-mediated nephritis (DI-IMN) has become a more widely known cause of acute kidney injury (AKI), with the potential for development to chronic kidney disease if not detected and treated promptly. T-cell hypersensitivity to pharmaceuticals, such as antibiotics, proton pump inhibitors, nonsteroidal anti-inflammatory drugs, and immunological drugs, are the major causes for it. Beyond clinical burden, DI-IMN reflectsintricate molecular interactions that sustain interstitial inflammation and tubular injury. These interactions include haptenization and neoantigen creation, antigen presentation, costimulatory signaling, and cytokine–chemokine networks. Conventional biomarkers, such as proteinuria and serum creatinine, are not sensitive enough to detect early diseases. Novel urine and serum indicators (such as soluble CD163, NGAL, MCP-1, and KIM-1) and multi-omics techniques provide better phenotyping, therapy monitoring, and earlier detection. Renal biopsy with immunophenotyping remains the diagnostic cornerstone, but the combination of genetic profiling, pharmacogenomics, and AI- based risk models promises more precise, less intrusive approaches. This review synthesizes epidemiology, immunopathogenesis, and drug-specific patterns of DI-IMN, highlighting diagnostic challenges and translational opportunities. We emphasize early drug withdrawal and timely immunosuppression to enhance renal recovery, along with reno-protective measures. Future directions focus on personalized medicine, and real-time monitoring is required to mitigate long-term renal morbidity and improve patient outcomes who are exposed to high-risk medications.
Keywords: Cytokine–chemokine; Personalized medicine; T-cell; immune reaction; nephritis